The Drivers and Impacts of Water Infrastructure Reliability : A Global Analysis of Manufacturing Firms - Islam, Asif; Hyland, Marie (World Bank, Washington, DC, 2018)
Inadequate infrastructure impedes the productivity of manufacturing firms, with negative consequences for the wider economy. This study examines how water infrastructure copes with severe weather fluctuations and analyzes the effect of unreliable water supplies on the productivity of manufacturing firms, focusing predominately on firms in developing economies. This is achieved using firm-level data from World Bank Enterprise Surveys covering more than 16,000 manufacturing firms in a cross-section of 103 countries between 2009 and 2015. The study finds that periods of significantly low rainfall lead to higher water outages, and that the overall impact is driven by the effects of drought on low-income and lower-middle-income economies, with upper-middle-income and high-income economies benefitting from more resilient water infrastructure. Furthermore, the study finds that incidents of water outages lead to lower firm productivity for firms in less developed economies. For the average firm located in a low-income or lower-middle-income economy, one additional water outage incident per day in a typical month can lead to losses of approximately 8.2 percent of annual sales. This finding calls for increased policy focus on water infrastructure services, particularly in poorer countries where water infrastructure and firms seem to be particularly vulnerable to the vagaries of rainfall.